Strategi Menyusun Manuver Arsip yang Efektif di Dispusdik Malang - Brilian Musthafa Pasha; Joni Dwi Pribadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine the effective archive maneuver strategy at Dispusdik Malang. The method in this study is field research with a qualitative approach. The data used in this study were obtained through direct observation, interviews with Dispusdik Malang employees involved in archive management, and literature studies on good archive management. Interviews were conducted with several officials who have responsibilities in the field of administration and archive management. In addition, this study also involved an analysis of the archiving system currently used by Dispusdik Malang, both in manual and digital forms. The results of the study indicate that effective archive management is highly dependent on the systematic application of four main stages, namely sorting, grouping, describing, and creating archive schemes. Overall, these four components are interrelated and support the creation of an efficient, transparent, and accountable archive management system. With proper implementation, organizations can improve the quality of information services, maintain data integrity, and support decision-making processes based on accurate and reliable data.